PERENCANAAN GEDUNG PARKIR MOBIL TIGA LANTAI DENGAN MENGGUNAKAN STRUKTUR BETON DI AREA DEPO MRT JAKARTA: DESIGN OF THREE FLOOR CAR PARKING BUILDING USING CONCRETE STRUCTURES IN THE DEPO AREA OF MRT JAKARTA - Fatmawati Oemar; Feri Panca Rama Dani (FTSP Universitas Jayabaya, 2021)
The Jakarta MRT depot is experiencing increasing development. Currently, the car park area at the Jakarta MRT Depot is not functioning properly due to the lack of available land, so that many four-wheeled vehicles are parked inappropriately. To overcome these problems, it is necessary to build a car parking area at the Jakarta MRT Depot. The plan is to build a parking building with an area of 6,656 m2, a parking angle design of 90°, a reinforced concrete structure consisting of two floors. The beam dimensions are 650 mm x 500 mm, the column dimensions are 500 mm x 500 mm and the plate thickness is 200 mm. The parking building can accommodate as many as 400 four-wheeled vehicles. In planning the car park building, data are used, including the results of ground sondir. Analysis of calculations using the SAP2000 Version20 design and structure application.